KOMUNITAS SERANGGA AIR DI SUNGAI HUTAN KETAMBE, TAMAN NASIONAL GUNUNG LEUSER, ACEH. - WIRJOATMODJO, S.; ATMOWIDJOJO, ANITA HANNA (Research Center for Biology-Indonesian Institute of Sciences, 1985)
S. WIRJOATMODJO & ANITA HANNA ATMOWIDJOJO. 1985. Insect community of stream ecosystem of Ketambe forest, Gunung Leuser National Park, Aceh, Berita Biologi 3.(3) : 111 -115.Non-strictly seasonal study on the insect community of stream ecosystem at Ketambe forest, Gunung Leuser National Park,Aceh was undertaken from September 1980 to February 1983,with the aim of providing base line data of the local stream ecosystem. Thirty two species of benthic insects were recorded from the depth between 5–30 cm.They belong to the orders of Diptera, Odonata, Kphemeroptera, Coleoptera, Plecoptera, Hemiptera, Megaloptera and Trichoptera. The number of species found was higher during the beginning of the dry than that of the rainy season (96,9% vs 59,4% of the total). Diptera and Odonata showed the highest number of species (8) among the orders, whereas Trichoptera was the lowest (one species). However, in term of frequency of occurence and abundance, the Trichoptera species, Hydropsyche sp,, was the highest, followed by Neoperla sp. (Flecoptera). There was a tendency of seasonal fluctuation in species number and life cycle in several species. Bottom structures containing pebbles, boulders of various sizes and leaf litter for shelter and feeding site, appeared to be the best habitat. Species composition or number varied with stations. However, diversity indexes among stations were more or less similar, and all of them were low.